IMPORTANCE OF THE IMPLEMENTATION OF A MANAGEMENT MODEL IN THE TRADITIONAL FISHING CANTON MANTA, ECUADOR. - Lara Ocaña, Juan Carlos (2015)
An important group of the Ecuadorian population is linked to the artisanal fisheries where most of the fresh fish consumed in the country originates. In the canton Manta, there are approximately 5,000 registered boats known as fibers, which are essential for fishing; however, in the last four years artisanal fishermen have endured massive economic losses by theft of fishing gear and engines at sea, a situation that sometimes it’s even mortal for the crew. The research is based on the situational analysis of artisanal fisheries and the existing problems in the management of its activities, proposing the implementation of a management model to decrease piracy on the high seas and solve other problems related to it. The main Objective of this work is to propose a model to improve the management of artisanal fisheries in Canton Manta.